Análisis histórico de la educación en la ciudad de Loja como medio para revalorizar la identidad y la cultura - Reinoso Acaro, Franco Aníbal (2022)
The research is approached from the point of view of Emilio Durkheim, who maintains that education is a historical-social-cultural phenomenon, decisive for the development of peoples; Within this framework, the general objective of the research was to analyze the historical evolution of education in the city of Loja in the federal government, through bibliographic research to revalue identity and culture. The approach used was qualitative, the type of research was bibliographic and descriptive, which allowed analyzing the historical evolution of education, characterizing it as a socio-historical-cultural phenomenon; and, chronologically systematize the historical facts of Ecuadorian education that contributed to the development of Loja education in the federal government. In the development of the work, the methods were used: scientific, inductive - deductive and descriptive, as a technique the unstructured interview was used, which served to collect data and contributions from an outstanding qualified informant that was later strengthened with documents from renowned local historians and nationals. The fulfillment of the proposed objectives, allow us to maintain that, indeed, education is a historical, social, cultural and hermeneutical - dialectical phenomenon, because each stage of the history of each society has its own characteristics, customs, traditions, ways of thinking. and civic, ethical, political and moral values that contribute to the revaluation of identity and culture. Therefore, it is concluded that education is a historical - social - cultural phenomenon because theoretical - methodological constructs are involved in it, aligned with the conservation of culture, diversity, social work, in scenarios of moral ethics, interculturality, conscience collective, dimensions that make up social identity. From this vision, education is decisive for the development of a community and of peoples in general. Keywords: historical evolution of Loja, education in Loja, historical phases in Loja, Lojan culture